2018
DOI: 10.2478/pjct-2018-0054
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and optimization of spectrophotometric colour removal from dye containing wastewater by Coagulation-Flocculation

Abstract: The performance of Vigna unguiculata coagulant (VUC) for colour removal from acid dye was investigated in this study. The proximate, structure and morphology of the coagulant were investigated using standard offi cial methods, Fourier-Transform Infrared (FTIR) spectrometer and scanning electron microscopy (SEM), respectively. Response surface methodology (RSM) using face-centred central composite design (FCCD) optimized four process variables including pH, coagulant dosage, dye concentration and time. The colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The applicability of thermally activated sodium persulfate (SPS) for the degradation of Acid Blue 92 (AB92) from its aqueous solution was investigated. The effects of pH (3)(4)(5)(6)(7)(8)(9)(10)(11), temperature (298-333 K), contact time (15-75 min), SPS concentration (0.05-0.5 mM), and initial AB92 concentrations (50-400 mg/L) on the degradation of AB92 were examined. The AB92 disintegration kinetics was studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The applicability of thermally activated sodium persulfate (SPS) for the degradation of Acid Blue 92 (AB92) from its aqueous solution was investigated. The effects of pH (3)(4)(5)(6)(7)(8)(9)(10)(11), temperature (298-333 K), contact time (15-75 min), SPS concentration (0.05-0.5 mM), and initial AB92 concentrations (50-400 mg/L) on the degradation of AB92 were examined. The AB92 disintegration kinetics was studied.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of different parameters such as pH (3, 5, 7, 9, and 11), contact time (10,20,40,60, and 80 min), dye concentration (50,75,100,150, and 200 mg/L), SPS concentration (0.05, 0.07, 0.09, 0.3, and 0.5 mM), and temperature (313, 323, 333, 343 and 353 K) on AB92 degradation were studied. Initially, the initial AB92 dye concentration, SPS concentration, pH, and temperature were set to be constant at 200 mg/L, 0.07 mM, 3, and 333 K, respectively.…”
Section: Experimental Procedures and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, wastewaters containing this type of dyes were highlighted as one of the most important threatening factors in environmental and public health [2,5]. Different studies have reported that there are several methods for removing dyes from textile wastewaters, including the application of photodecomposition [6], electrolysis [7,8], adsorption [9][10][11][12][13][14][15][16][17][18], oxidation [19], biodegradation [20], combined sonochemical and adsorption [21], coagulation-flocculation [22,23], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Coagulation is an indispensable part of traditional water treatment technology and plays an important role in removing turbidity, Chroma, and pathogenic microorganisms (Obiora-Okafo & Onukwuli, 2018;Oraeki, Skouteris, & Ouki, 2018). At present, the main research directions of coagulation technology are to develop new coagulants, optimize process parameters, and develop coagulation-based combined treatment process.…”
Section: Coagulationmentioning
confidence: 99%